Translation, transcultural adaptation, and validation of the Serbian version of the PSS-QoL questionnaire – a pilot research - Vujović, Sanja; Desnica, Jana; Mijailović, Sara; Milovanović, Dragan (Vojnosanitetski pregled, 2023)
Background/Aim. The assessment of health-related quality of life (HRQoL) is fundamental for a better understanding of the effect of a disease on different aspects of a patient’s daily functioning and the efficacy of the treatment modalities. Primary Sjögren’s Syndrome (SS) Quality of Life Questionnaire (PSS-QoL) is the first disease-specific instrument for evaluating HRQoL in patients with primary SS. The aim of this study was to formally translate the PSS-QoL questionnaire from English to Serbian, assess its psychometric properties, and validate it for use in the Serbian population. Methods. The research was designed as a pilot study and included 30 participants. Internal consistency was determined by calculating Cronbach’s alpha coefficient. The construct validity of the questionnaire was estimated by the correlation of its overall result with the patients’ EuroQoL-5D, European League Against Rheumatism (EULAR) SS Patient Reported Index, Oral Health Impact Profile-14, and Emotion Regulation Questionnaire scores. Results. There were 29 (96.7%) female participants and one (3.3%) male participant in the research. The average (± standard deviation) score of PSS-QoL was 44.63 ± 12.901 at baseline and 41.70 ± 12.075 at follow-up. Cronbach’s alpha value of the Serbian version of PSS-QoL was 0.922. The test-retest intraclass correlation coefficient was 0.981 (95% confidence interval: 0.436–0.996). Analysis revealed a statistically significant moderate to strong correlation between PSS-QoL scores and EuroQol-5D (rs = -0.696), EULAR SS Patient Reported Index (rs = 0.883), and Oral Health Impact Profile-14 scores (rs = 0.809). Conclusion. Serbian adaptation of the PSS-QoL instrument can be used to evaluate HRQoL of patients with primary SS both in academic research and clinical practice as a novel outcome measure.
Keywords: quality of life; serbia; sjogren’s syndrome; surveys and questionnaires; translations